The Work Performance Analysis of Sea Fishing in Kolaka Regency - Rauf, Rusdiaman; Tawe, Amiruddin; Rakib, Muhammad (International Review of Management and Marketing, 2017)
The purpose of this study is (1) to analyze the direct effects of work motivation, risk taking, entrepreneurship learning and individual commitment to work performance; (2) to analyze the indirect influence of work motivation, risk taking, entrepreneurial learning through individual commitment to the work performance. This study uses a survey with a sample of 125 respondents. The data were analyzed using Path Analysis. The results showed that (1) work motivation, risk-taking, and individual commitment at significantly influences on work performance, while the entrepreneurship learning does not significantly influences; (2) risk-taking and entrepreneurial learning indirectly influences to individual commitment and significantly influences the business performance, while work motivation to individual commitments indirectly gives no significant effect on work performance. Keywords: Work motivation, risk taking, entrepreneurship learning, individual commitment, and work performance. JEL Classifications: L, L26